Pengaruh Pemberlakuan Rapid Test Terhadap Kepuasan Penumpang pada Era New Normal di Bandar Udara Internasional Adi Soemarmo Solo - Vidia kusuma (PT FORMOSA CENDEKIA GLOBAL, 2022)
The Covid-19 virus is a pandemic has lasted from December 2019 until now, at this time Covid-19 is declared to have become endemic because the handling can be controlled. The Covid-19 virus pandemic that occurred hhad an impact on the air transportation mode sector due to the rapid soread of the Covid-19 virus. Rapid test sereological is on of the methods to detect whether there is Covid-19 virus transmission in a person’s body. This study aims to determine how much influence the implementation of the Rapid test has on passenger satisfaction in the new normal era at Adi Soemarmo International Airport, Solo. This study uses quatitative reserch by distributing questionnaires to a sample of 96 respondents to all passengers at Adi Soemarmo Airport solo, in analyzing the data the instruments used are validity test, reliability test, simple linier test, t test and R square determination test. The results of this indicate that there is a significant effect between the influence of the Rapid test on passenger satisfaction and evidence that it has The results of determinant coefficient in this study obtained a determinant value of 0,389 which means that magnitude of the effect of the variable rapid test (X) on the passenger satisfaction variable (Y) is 38,9% at Adi Soemarmo International Aiport Solo.